2016
DOI: 10.1007/s10120-016-0668-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-institutional prospective feasibility study to explore tolerability and efficacy of oral nutritional supplements for patients with gastric cancer undergoing gastrectomy (CCOG1301)

Abstract: Background Postoperative malnutrition after gastrectomy is deemed inevitable, which could have prejudicial influence on survival for gastric cancer patients. A prospective feasibility study was conducted to evaluate the efficacy of postoperative oral nutritional supplements. Methods Stage I-III gastric cancer patients who underwent distal or total gastrectomy received oral administration of Racol Ò NF (Otsuka Pharmaceutical Factory, Japan), a liquid enteral nutritional formula, as a supplement to regular meals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 23 publications
3
50
0
Order By: Relevance
“…As sarcopenia is associated with higher rates post-operative morbidity and mortality and poor long-term survival, perioperative interventions are important to reduce these risks. One study in this review reported benefits of oral nutrition supplement to reduce weight loss in the post-operative setting [28]. However, this study did not evaluate its impact on surgical outcomes and long-term survival.…”
Section: Discussionmentioning
confidence: 93%
“…As sarcopenia is associated with higher rates post-operative morbidity and mortality and poor long-term survival, perioperative interventions are important to reduce these risks. One study in this review reported benefits of oral nutrition supplement to reduce weight loss in the post-operative setting [28]. However, this study did not evaluate its impact on surgical outcomes and long-term survival.…”
Section: Discussionmentioning
confidence: 93%
“…Of note, despite the very short period of intervention, this study showed that preoperative nutritional exercise interventions can be effective. Kobayashi et al have conducted a prospective study to evaluate the efficacy of postoperative oral nutrition supplements in Japan (54). Their results showed that postoperative nutritional supplementation can also lead to a significant reduction of body weight loss for gastrectomized patients.…”
Section: The Influence Of Sarcopenia On Postoperative Outcomes Of Gasmentioning
confidence: 99%
“…A randomized controlled study showed that taking ONS for 12 weeks after surgery could prevent patients with gastric cancer from losing 1.1 kg (2% of body weight; Hatao et al, 2017). The benefits of ONS are obvious, but the effects of ONS seem to be dose‐dependent (de van der Schueren et al, 2018; Dias Rodrigues et al, 2017; Kobayashi et al, 2017); therefore, the main factor in the effect of ONS is patient compliance. However, compliance with ONS is not satisfactory; for example, Grass et al reported that patient compliance with ONS was as low as 42% (Grass et al, 2015).…”
Section: Introductionmentioning
confidence: 99%